2016
DOI: 10.1017/ice.2016.105
|View full text |Cite|
|
Sign up to set email alerts
|

Assessment of Time to Clinical Response in Patients with Sepsis Treated Before and After Implementation of a Matrix-Assisted Laser Desorption Ionization Time-of-Flight Blood Culture Identification Algorithm

Abstract: OBJECTIVE To evaluate time to clinical response before and after implementation of rapid blood culture identification technologies. DESIGN Before-and-after trial. SETTING Large, tertiary, urban, academic health-sciences center. PATIENTS Patients >18 years old with sepsis and concurrent bacteremia or fungemia were included in the study; patients who were pregnant, had polymicrobial septicemia, or were transferred from an outside hospital were excluded. INTERVENTION Prior to the intervention, polymerase chain re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 25 publications
(54 reference statements)
1
12
0
1
Order By: Relevance
“…However, the infecting bacteria investigated by Hansen et al were relatively rare Gram-positive cocci, such as Ruminococcus species 11. Furthermore, treatment following rapid organism identification by TOF-MS has been shown to lead to reduced mortality in severe sepsis cases after implementation of TOF-MS in combination with BC 14. Furthermore, TOF-MS recently has been shown to reduce the use of wide-spectrum antibiotics in infection control when employed as part of an antimicrobial stewardship program 15.…”
Section: Discussionmentioning
confidence: 99%
“…However, the infecting bacteria investigated by Hansen et al were relatively rare Gram-positive cocci, such as Ruminococcus species 11. Furthermore, treatment following rapid organism identification by TOF-MS has been shown to lead to reduced mortality in severe sepsis cases after implementation of TOF-MS in combination with BC 14. Furthermore, TOF-MS recently has been shown to reduce the use of wide-spectrum antibiotics in infection control when employed as part of an antimicrobial stewardship program 15.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that MALDI-TOF MS combined with an ASP improved clinical outcomes in patients with positive blood cultures [ 12 18 ]. Huang et al [ 13 ] reported that the use of MALDI-TOF MS combined with an ASP in patients with bacteremia and candidemia was associated with improved clinical outcomes, including the time to effective therapy (30.1 vs. 20.4 h, P = 0.021), 30-day all-cause mortality (20.3% vs. 12.7%, P = 0.021), and length of intensive care unit (ICU) stay (14.9 vs. 8.3 days, P = 0.014) in univariate analyses, and that ASP introduction was related to a nonsignificant trend toward reduced mortality (odds ratio, 0.55; P = 0.075) in multivariate analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with traditional biochemical methods, MALDI‐TOF MS offers substantially faster and more accurate identification of isolated organisms . Several studies have shown that MALDI‐TOF MS combined with an antimicrobial stewardship program (ASP) improves clinical outcomes in patients with positive blood cultures . However, in many hospitals around the world, ASPs are not in place because of restrictions on medical resources .…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] Several studies have shown that MALDI-TOF MS combined with an antimicrobial stewardship program (ASP) improves clinical outcomes in patients with positive blood cultures. [8][9][10][11][12][13][14] However, in many hospitals around the world, ASPs are not in place because of restrictions on medical resources. 15 Furthermore, Jeon et al reported that evaluation using MALDI-TOF MS in the absence of an ASP does not improve clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%